Nivolumab treatment in advanced non-small cell lung cancer: real-world long-term outcomes within overall and special populations (the UNIVOC study). (October 2020) - Assié, Jean-Baptiste; Corre, Romain; Levra, Matteo Giaj; Calvet, Christophe Yannick; Gaudin, Anne-Françoise; Grumberg, Valentine; Jouaneton, Baptiste; Cotté, François-Emery; Chouaïd, Christos
Objective: To describe long-term outcomes of patients treated with nivolumab for advanced non-small cell lung cancer (aNSCLC) in everyday clinical practice in France, with a focus on patients aged ⩾80 years, patients with renal impairment and patients with brain metastases. Methods: The study included all patients with aNSCLC recorded in the French national hospital database, starting nivolumab in 2015–2016 and followed until December 2018. Patients were stratified by age, the presence of renal impairment and brain metastasis, as documented in the hospital discharge summaries. Information was retrieved on demographics, comorbidities and treatment history at baseline. Time to discontinuation of nivolumab treatment and overall survival were estimated using Kaplan–Meier survival analysis. Results: Overall, 10, 452 patients were included, of whom 514 were octogenarians, 479 had renal impairment and 1800 had brain metastases at baseline. Median duration of nivolumab treatment was 2.8 months in the overall population and in both the octogenarian and renally impaired subgroups, and 2.3 months in patients with brain metastases. Median overall survival in these patient groups was 11.7 months (95% confidence interval: 11.3–12.2), 11.7 months (11.3–12.1), 11.7 months (11.3–12.2) and 9.9 months (9.0–10.9) respectively. Three-year overall survival rates were 19.1% (18.1–20.2) in the overall population, 16.5% (11.6–23.4) in octogenarians, 15.9% (11.8–21.4) in patients with renal impairment and 21.7% (19.4–24.2) in those with brain metastases. Conclusion: This large nationwide retrospective real-life cohort provided narrow estimates of long-term overall survival, which reached 19% at 3 years, consistent with data from phase III trials of nivolumab. Survival rates were comparable in the three special populations of interest and the overall population.